2020
DOI: 10.3390/buildings10030043
|View full text |Cite
|
Sign up to set email alerts
|

Welds Assessment in K-Type Joints of Hollow Section Trusses with I or H Section Chords

Abstract: The use of hollow section structures has received considerable attention in recent years. Since the first publication of CIDECT (International Committee for the Development and Study of Tubular Structures), additional research results became available, especially concerning the design of welds between members of trusses joints. To assess the capacity of welded joints of trusses between braces made of hollow sections and I-beam chords, the effective lengths of the welds should be estimated and their location ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…The buckling area occurred on the steel, and the welded joint was not in a weak position, so the weld did not weaken the load-bearing capacity of the specimen. Relevant studies showed that high-quality welds had some influence on the location of the buckling deformation, and generally had little impact on improving load-bearing capacity [26,27].…”
Section: Test Results and Analysismentioning
confidence: 99%
“…The buckling area occurred on the steel, and the welded joint was not in a weak position, so the weld did not weaken the load-bearing capacity of the specimen. Relevant studies showed that high-quality welds had some influence on the location of the buckling deformation, and generally had little impact on improving load-bearing capacity [26,27].…”
Section: Test Results and Analysismentioning
confidence: 99%
“…This block ends with article [21]. It is easy to notice that the hollow section structures embellish architecture.…”
Section: Contributionsmentioning
confidence: 96%
“…It is easy to notice that the hollow section structures embellish architecture. The article by Broniewicz and Broniewicz [21] is devoted to this issue, offering designers the most up-to-date information on welds for so-called lap joints. The article is addressed to designers of steel structures and is directly applicable in determining the quality of joints between bars of truss connections.…”
Section: Contributionsmentioning
confidence: 99%